Multi-dimensional perspectives on sustainability in domestic waste management - Y. Ismail; R. Adji; A.D. Santoso; S. Wahyono; M.A. Kholiq; T. Handayani; S.D.R. Pahri; S. Putiamini; R.A. Pratama; F. Nurfatriani; F.L. Sahwan; F. Suryanto; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Sustainable waste management is a critical global challenge, demands a multifaceted approach to evaluate and boost its effectiveness. This study evaluates the sustainability of domestic waste management using a multi-dimensional scaling framework, focusing on five fundamental parameters,such as environmental, economic, social interactions, technological, and regulatory sustainability. This study aims to pinpoint key leverage points for focused enhancements, promoting sustained resilience and efficiency within the system.METHODS: A mixed-method approach was employed, combining literature reviews, research journal analysis, and initial data collection. Standardized surveys and focus group discussions were performed with stakeholders, including plant operators, managers, and experts. The rapid appraisal tool for waste management was used to assess thirty-three sustainability attributes, with responses measured using a Likert scale. The results were classified into four sustainability levels: unsustainable, less sustainable, fairly sustainable, and sustainable, which facilitated a structured analysis of the system’s performance.FINDINGS: The analysis indicates moderate sustainability across all dimensions, with economic sustainability scoring the highest at 55.27 percent signifying its role as the system's backbone. Nonetheless, there is a significant need for advancement in the areas of financial management and leadership. Technological sustainability followed at 54.44 percent, reflecting incremental advancements but underscoring the need for innovative waste treatment technologies. With a score of 52.12 percent, social sustainability reflects significant community engagement but also uncovers shortcomings in environmental education. The environmental dimension scored 47.1 percent, with leadership and inter-institutional cooperation emerging as under-utilized yet crucial factors. Ranking at a mere 45.1 percent, institutional sustainability was the lowest, indicating an urgent demand for effective governance structures and enhanced inter-agency collaboration.CONCLUSION: Strengthening institutional frameworks through leadership development and formalizing inter-agency partnerships is essential for improving sustainability. Economic resilience can be fostered by incentivizing community-based waste management through grants and subsidies. Additionally, targeted public education and community engagement initiatives can bridge social sustainability gaps. The system exhibits a fair amount of progress; however, it is vital to undertake strategic actions to secure long-term sustainability and ensure it aligns with global environmental objectives.